Kalman Filter Based Formaldehyde Odor Characteristics Estimation in Pathology Department, HTAA - Hamzah, Ahmad; Nor Syahidah, Samsuri; Mohd Rusllim, Mohamed (2015)
This paper deals with Kalman Filter based estimation for formaldehyde odor characteristics for Pathology Department in HTAA. Currently, the formaldehyde can only be measured by using an e-nose alone which is still a new technique for measurement and the enose has limited performance due to specific jig dimension and environment conditions. Hence, there is a need to estimate the characteristics that able to simulate different environment conditions. The proposed design are referring to the raw data obtained from real experiment of four different sensors measurement from e-nose. The mathematical model is then constructed in a state space representation based on the raw data to approximate the nearest possible estimation. Simulation analysis described that the approach is novel which can estimate the formaldehyde odor characteristics with small error. The developed model also open the possibilities to infer the conditions of formaldehyde for different kinds of environment.